Variations of the chemical characteristics and source regions of aerosols at the Cape Point GAW station - Spence, Kurt (Department of Oceanography, 2022)
Nitrogen is an essential component for life. The natural nitrogen cycle has been greatly disturbed by the production of fertilizer and use of fossil fuels, such that it has doubled the amount of reactive nitrogen (Nr) produced globally. Excessive additions of Nr to the environment can have negative effects, including eutrophication, loss of biodiversity, enhanced greenhouse gas emissions, acidification, increased tropospheric ozone, and damage to human health. Excess ammonia (NH3) and nitrogen oxide (NOx) emissions lead to increased aerosol loading via secondary aerosol formation processes. Increased aerosol loading has impacts on the climate and on human health. Furthermore, the aerosols formed from Nr from continental sources can get deposited to the open ocean, which is usually nitrogen limited. Knowing the concentrations of different aerosol species from a pollution free environment, such as the remote open ocean, can give insights into the natural preindustrial conditions and be used as a baseline for looking into the impacts of anthropogenic activities. This thesis focuses on establishing the Cape Point Global Atmosphere Watch (GAW) station as a site for collecting aerosol samples from pristine marine air masses. The use of a tower site allows for high temporal resolution sampling across multiple seasons and years, which is logistically difficult when relying on ship-based sampling of pristine marine environments. Results are presented from the chemical composition analysis of aerosols sampled at the Cape Point GAW station, including comparisons of two different aerosol sampling systems (tall-tower PM10 and ground-based sizesegregated). Furthermore, the installation and testing of a sector-controlled sampling system designed to reduce continental influence on samples is evaluated. Air mass back trajectories and radon (222Rn) concentrations were used to classify the air masses of each aerosol sample as either marine, modified marine, or continental. We found that continental samples had elevated concentrations of NH4 + , NO3 - , and non-sea-salt SO4 2- , whereas the marine samples had elevated concentrations of Cl- , and Na+ , as expected. A comparison of the tall-tower PM10 and ground-based size-segregated sampling systems showed that the ground-based sampler measured higher concentrations of coarse mode aerosols. This is attributed to the settling of large aerosols within the long sampling intake tube from the tower sampling system. The sector-controlled sampling system based on wind speed and direction was able to remove some of the influence of continental air masses, however some continental influence could not be avoided as the continental air masses circulated over the ocean before being sampled from the marine sector. This system could be improved by having additional cut-off limits defined for sampling, such as particle number, black carbon, or carbon monoxide (CO) concentrations.